Thermal comfort analysis of fred‑clay brick, cement‑sand block and cement stabilized earth block masonry house models - Sathiparan, N.; Daniel, N.S.; Malsara, K.G.N.; Akmal, M.S.M. (Springer, 2022)
Fired-clay brick, cement-sand block and cement stabilized earth blocks are the most commonly used material for masonry construction in Sri Lanka. Strength, durability and cost are three major factors that infuence the selection of material for wall construction. Even though Sri Lanka has a tropical climate, the benefts of insulating the external walls of the house are often not considered. Apart from thermal comfort of the internal environment, there is concern regarding increase in energy consumption. However, in recent years, as awareness of sustainable and green building concepts increased, interest in using sustainable and thermal comfort materials for house construction has increased. Because external walls play a major role in thermal insulation, there is a need to select suitable wall materials that can be energy efcient and reduce cooling load. Therefore, the present study aims to understand thermal comfort in house units constructed with commonly used wall mate- rial such as fred brick, cement-sand block and cement stabilized earth block. Temperature and humidity inside and outside house models were observed to compare the impact of masonry materials on thermal comfort. To compare the thermal com- fort performance of the house models, three thermal comfort analysis models: steady-state comfort model, adaptive criteria model and deterministic models were used according to the British Standard European Norm (BS EN) 16798, CIBSE TM52 and ANSI/ASHRAE 55. Results show that house units constructed with cement stabilized earth blocks and fred-clay bricks are significantly more comfortable in terms of temperature and humidity variations. Energy-efficient house units thereby minimized energy consumption through reduction in indoor temperature. Therefore the cement stabilized earth block and fred-clay brick house model are found to be a suitable choice for construction.
Keywords: Masonry; Bricks; Cement-sand blocks; Cement stabilized earth block; Thermal comfort